Mentalization-based psychotherapy with a child with asd: preliminary results - Martín Meoqui; Alar Urruticoechea (INFAD)
Autism Spectrum Disorder (ASD) is associated with deficits in mentalization and emotional regulation. Mentalization-Based  Treatment for Children (MBT-C) aims to improve these functions through individual interventions with the child and coordinated work with parents and educators. These interventions seek not only to enhance the child’s clinical functioning but also to promote systemic changes in their everyday environment. A multimodal intervention was implemented for a 10-year-old child with ASD in a specialized educational center, combining weekly MBT-C psychotherapy sessions, intensive educator training, and parental guidance sessions. Quantitative instruments (HoNOSCA for educators and CGAS for the psychotherapist) and qualitative interviews with parents were employed. Pre-post analyses were conducted using Student’s t-tests, Wilcoxon tests, and CRB estimation. Although pre-post differences did not reach statistical significance, moderate to large effect sizes were identified in key variables such as disruptive behavior, attention, academic skills, and emotional symptoms. Parents and educators reported notable improvements in emotional regulation, autonomy, social adaptation, and strengthening of affective bonds. The findings suggest that a mentalization-based intervention involving key educational and familial agents can facilitate clinically relevant improvements in children with ASD, even when traditional statistical evidence is inconclusive.